Prototype Pemantau Suhu dan Penyiraman Green House dengan Wemos Berbasis IOT - Reni Veliyanti; Dani Sasmoko (Universitas Ivet, 2021)
Green House managers are experiencing problems due to changes in climate which are very sudden and extreme nowadays, this has resulted in damage to ornamental plants. Therefore, a system that is able to monitor temperature and humidity levels in the air is needed so that ornamental plants can maintain their beauty. Research also developed an automatic watering system using Arduino and Wemos with a firebase database that can ease watering work. In testing the tool runs smoothly even though there is a slight difference in temperature readings but the flushing device can flush accordingly at 7 am and the fan runs when the temperature exceeds 270C to cool the room.